Wireless hacks - Flickenger, Rob (O'Reilly, 2005)
The authors bring readers more of the practical tips and tricks that made the first edition a runaway hit. Completely revised and updated, this version includes over 30 new hacks, major overhauls of over 30 more, and timely adjustments and touch-ups to dozens of other hacks.